Philosophical Theology as a Catalyst for Inclusive Interreligious Dialogue in Plural Societies - Widiyaningtyas, Ester; Christi, Areyne; Nicolaides, Angelo; Ming, David (Jurnal Theologia, 2025)
In an era of intensifying religious diversity and sociopolitical polarisation, interreligious dialogue is both a necessity and a moral imperative. However, such dialogue is often constrained by epistemological biases, theological exclusivism, and rigid doctrinal frameworks. This study explores the role of philosophical theology as a transformative medium for inclusive interreligious communication. Drawing on biblical values such as love, justice, and peace, and informed by dialogical approaches from Islamic (ta’aruf) and Jewish (“I-Thou”) traditions, the research proposes a pluralistic theological model grounded in epistemic humility and shared ethics. Utilising a descriptive-analytical method through systematic literature review of 50 scholarly works, the study demonstrates how philosophical reflection can overcome confessional barriers, reframe hermeneutical practices, and support practical initiatives—such as scriptural reasoning and alternative media—for sustainable dialogue. The research contributes theoretically by expanding the framework of dialogical theology, and practically by offering tools for interfaith actors and educators to foster ethical, inclusive, and context-sensitive engagement. This approach affirms that theological plurality, when anchored in philosophical depth, can generate transformative interreligious understanding in plural societies.